Effects of inflation and interest rates on land pricing. - Harmon, Jacob (Kansas State University, 2011)
Land is typically the highest value category of assets that farmers and ranchers have on their balance sheets. The value of land is affected by inflation. Understanding the effect of inflation on the land market helps farmers make better land pricing decisions and better asset management decisions. Using Treasury Bills and Farm Credit Bonds, future inflation expectations and agricultural risk premiums can be estimated. With the recent government stimulation of the economy and the resulting large amount of money infused into the economy, inflation is becoming an increasing concern with investors. Economic theory suggests that this infusion of money will affect future interest rates and ultimately the value of land given the inverse relationship between interest rates and the value of land. These lingering affects occur with the rise and fall of yield rates for Treasury Bills and Farm Credit bonds. Farm Credit bonds are sold at a premium over Treasury Bills. This premium indicates the market-assessed additional risk that farmers have to pay for their operating loans and other mortgages. Even though land values are affected by inflation, other things affect land values such as recreational use, development, and natural resource exploration. A combination of inflation and these other affects can greatly affect land prices.
Keywords: Farmland; Interest Rates; TIPS - Treasury Inflation Protected Securities; Inflation; Farm Credit Bonds; Agriculture, General (0473); Business (0310); Economics (0501)